Evaluating pavement performance in bus rapid transit systems: Lessons from Seoul, South Korea - Sang-Yum Lee; Tri Ho Minh Le (Case Studies in Construction Materials, 2023)
The proposed research aims to systematically investigate the condition of bus stops throughout Seoul, a densely populated metropolitan area. The study involves conducting a survey of multiple bus stops, taking into consideration traffic volume and pavement damage type. Field tests using the Falling Weight Deflectometer are conducted in heavily damaged bus stop sections to evaluate the performance of the surface, subbase, and subgrade layers. Additionally, this research proposes a polymer-modified stone matrix asphalt mixture with a nominal maximum size of 10 mm (10 mm PSMA) to enhance the rutting resistance of bus stop pavements while ensuring compliance with dynamic modulus acceptance values. Laboratory tests including Hamburg wheel tracking and dynamic modulus tests are conducted to achieve this objective. The results reveal that inadequate quality of the surface layer is the main cause of bus stop pavement failure in Seoul, with the average FWD modulus of the asphalt layer falling below the standard requirement of 725 ksi (28 % lower), indicating a 'low' structural condition based on evaluation standards. This can be attributed to inappropriate gradation and overload issues during rush hour. The dynamic modulus test results show that the PSMA 10 mm mixture outperforms the conventional 13 mm mixture in the low-frequency range and shows comparable performance in the high-frequency range. The Hamburg wheel tracking test indicates that all proposed mixtures have settlement values below 5.5 mm and do not exhibit the stripping point phenomenon, indicating excellent rutting resistance. Notably, the 10 mm PSMA mixture demonstrates superior permanent deformation resistance compared to the 13 mm PSMA and 13 mm PMA mixtures (1.26–185 times lower). Overall, the proposed mixtures exhibit promising performance in mitigating fast degradation at bus stops.